OPTIMIZATION OF BEST CULTURAL CONDITIONS FOR HIGH PRODUCTION OF PHOSPHATE SOLUBILIZING ACTIVITY BY FLUORESCENT PSEUDOMONAS ISOLATED FROM NORMAL AND REPLANT SITES OF APPLE AND PEAR - THAKUR, DEEPSHIKHA; KAUR , MOHINDER; SHYAM, VINEET (The Bioscan, 2014)
Bacteria belonging to Pseudomonas genera are known to be efficient phosphate solubilizers. As the physiological and nutritional requirement of an organism is genetically predetermined, it is important to provide the appropriate nutrient sources and proper environment for optimal production of activity. So, in our study optimization and standardization of the cultural conditions for the optimum production of phosphate solubilizing activity has been done. From the results it is concluded that out of four media i.e. PVK, NBRI-P, NBRI-Y and Kings, the maximum average of P-solubilizing activity by fluorescent Pseudomonas strains isolated from the normal and replant sites of apple and pear was observed in NBRI-P at 48 h, with the maximum release of available phosphate i.e. 606 µg/ ml. Maximum average growth along with maximum P-solubilizing activity of all the isolates was obtained at 28 ºC and pH 7, with the maximum release of available phosphate i.e. 845 and 788 µg/ml respectively. The optimum concentration of TCP for maximum P-solubilizing activity is 5 g/l in NBRI-P medium with the maximum release of available phosphate i.e. 756 µg/ml.